Aorto-oesophageal fistula: a late complication of Boerhaave syndrome. Issue 7 (4th July 2019) - Chae, Raphael P; Johnson, Mary Ann; Robinson, Domenic; Hii, Michael W
Abstract : A 68-year-old woman presented with haematemesis and chest pain 3 months after a spontaneous oesophageal perforation. The patient rapidly progressed to a state of hypovolaemic shock and after resuscitation was found to have aorto-oesophageal fistula on CT aortogram. The patient was treated with a successful thoracic endovascular aortic repair.